The role of seminal fluid extracellular vesicles in human endometrial receptivity - Rodríguez Caro, H (2018)
Embryo implantation is a key limiting factor to In Vitro Fertilization (IVF) success, the main treatment of subfertility. A successful embryo implantation requires the endometrium to be receptive, which involves embryo-endometrium crosstalk, decidualisation, and modulation of the maternal immune system. Research data showed maternal exposure to seminal fluid improved clinical pregnancy rates. The seminal fluid contains extracellular vesicles that facilitate cell-cell communication through their cargo. This thesis aimed to investigate seminal fluid extracellular vesicles (SF-EVs) and their role in human endometrial receptivity. SF-EVs, isolated by ultracentrifugation, were characterised and purified using size- exclusion chromatography. SF-EVs ranged between 15 to 300 nm and were a heterogenous group of EVs. Four populations were described based upon morphology while protein expression identified three CD63+ SF-EV populations and suggested another four populations by co-localization and correlation studies respectively. Importantly, purified SF-EVs were demonstrated to be a good representation of physiological SF-EVs after analysing extracellular vesicles in unprocessed seminal fluid. The role of SF-EVs in endometrial receptivity was then investigated. Bio-maleimide labelled SF-EVs bound to Ishikawa cells (endometrial adenocarcinoma cell line) and primary endometrial epithelial and stromal cells. SF-EVs bound more to untreated than progesterone treated Ishikawa cells, and, unlike previously described for progesterone- treated cells, SF-EVs did not induce dephosphorylation of CREB S133 in untreated Ishikawa cells. In addition, SF-EVs enhanced endometrial stromal cells secretion of prolactin throughout the days of decidualisation and increased total HCK Tyr411 phosphorylation in non-decidualised stromal cells. Bio-maleimide labelled SF-EVs also bound to primary endometrial immune cells. CD4+ and CD8+ T cells bound more SF-EVs than NK cells and regulatory CD4+ T (Treg) cells showed higher SF-EV binding than non-regulatory CD4+ T cells. SF-EVs did not change CD3 and CD25 Treg cell expression levels, which are involved in T cell receptor (TCR) mediated activation. Endometrial Treg cells also did not increase TGF-β1 expression after TCR mediated activation. These DPhil thesis reports for the first time that SF-EVs interact with endometrial cells and play a role in endometrial receptivity suggesting they might be used as adjuvants to assist human embryo implantation in IVF. It also highlights the need for further research to understand endometrial Treg cellular physiology.